Numerical Simulation on Carbonation Depth of Concrete Structures considering Time- and Temperature-Dependent Carbonation Process - Jianxin Peng; Huang Tang; Jianren Zhang; Steve C. S. Cai (Advances in Materials Science and Engineering)
In order to further understand the carbonation process of concrete structures, the time- and temperature-dependent diffusion process of CO2 in concrete is simulated based on the law of the CO2 mass conservation, and a two-dimensional mass transfer equation is established for the CO2 diffusion in concrete. The concrete block is discretized into triangular elements, and the CO2 concentrations at different positions are calculated based on finite element method. A computational algorithm is programed through the Matlab platform. The time- and temperature-dependent property and difference of the CO2 concentration at different positions of the structure are considered in the proposed model. Then, an accelerated carbonation experiment is carried out using concrete blocks with different mix proportions to investigate the influence of the water-cement ratio and temperature on the concrete carbonation. The experimental results effectively verify the correctness of the finite element model, and the proposed finite element method reasonably simulates the concrete carbonation through calculating the carbonation in practical engineering compared with other methods in references. An experimental-numerical correlation has been performed. The ratio of carbonation depth at the corner of the concrete members to the other positions is about 1.35. The carbonation depth is increased about 1.9 times when the temperature changes from 20°C to 40°C.